(untitled) - Hill, L. A. (Oxford, 1965)
Training students to reproduce material they have listened to or read, this book contains short anecdotes, followed by a set of comprehension questions on the passage. It also includes a complete wordlist at the back.
Keywords: Tiếng Anh,English language; Kỳ thi, câu hỏi,vv,Examinations, questions, etc